2012
DOI: 10.1109/tsp.2012.2184538
|View full text |Cite
|
Sign up to set email alerts
|

Bernoulli Particle/Box-Particle Filters for Detection and Tracking in the Presence of Triple Measurement Uncertainty

Abstract: This work presents sequential Bayesian detection and estimation methods for nonlinear dynamic stochastic systems using measurements affected by three sources of uncertainty: stochastic, set-theoretic and data association uncertainty. Following Mahler's framework for information fusion, the paper develops the optimal Bayes filter for this problem in the form of the Bernoulli filter for interval measurements. Two numerical implementations of the optimal filter are developed. The first is the Bernoulli particle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…Various methods have been put forward to robustify the particle filtering algorithm for systems with unknown statistics. The box particle filtering, which combines sequential Monte Carlo method with interval analysis, has been introduced in [41][42][43]. Unlike the standard particle filtering method where particles are points in the state space and likelihood functions are defined by a statistical model, the box particle filter uses multidimensional intervals in the state space as particles and a bounded error model to evaluate the likelihood functions.…”
Section: Robust Particle Filtermentioning
confidence: 99%
“…Various methods have been put forward to robustify the particle filtering algorithm for systems with unknown statistics. The box particle filtering, which combines sequential Monte Carlo method with interval analysis, has been introduced in [41][42][43]. Unlike the standard particle filtering method where particles are points in the state space and likelihood functions are defined by a statistical model, the box particle filter uses multidimensional intervals in the state space as particles and a bounded error model to evaluate the likelihood functions.…”
Section: Robust Particle Filtermentioning
confidence: 99%
“…The box-PF algorithm is presented through the prism of the Bayesian inference using mixtures of uniform pdfs with boxed supports. More details about the box-PF and its implementation can be found in [3]- [5].…”
Section: Lessons Learned Further Reading and Future Avenuesmentioning
confidence: 99%
“…Indeed, in some applications where the sampling importance resampling (SIR) PF may require thousands of particles to achieve accurate and reliable performance, the box-PF can reach the same level of accuracy with just a few dozen box particles. Recent developments [4] also show that a box-PF can be interpreted as a Bayes' filter approximation allowing the application of box-PF to challenging target tracking problems [5].…”
mentioning
confidence: 99%
“…The box-particle filter was studied and explained through the Bayesian perspective by interpreting each box particle as a uniform probability density function (PDF) [10]. A single target box-particle Bernoulli filter with box measurements was presented in [11]. The box-particle PHD filter for multi-target tracking with an unknown number of targets, clutter and false alarms was derived in [12].The box-particle cardinality balanced multi-target multi-Bernoulli filter and its implementation was proposed in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [21] presents an implementation of box-particle filter on extended target. Various works have shown that the box-particle filter can reach a similar performance as the traditional particle filter with less computational complexity and runtime [11][12][13], [18].…”
Section: Introductionmentioning
confidence: 99%